Energy Consumption and Economic Growth in Nigeria: An Augmented Neoclassical Growth Model Perspective - ISHIORO, Bernhard O. (Journal of Environmental Management and Tourism, 2020)
This study applied the augmented Neoclassical growth model to the analysis of the relationship between consumption of energy and economic growth in the Nigerian economy. Five definitions of energy consumption were adopted viz: crude oil, gas, coal, electricity and total energy consumption. Apart from economic growth the study also used labour participation and capital accumulation within the framework of the Vector Auto-regression (VAR) and other estimation techniques. The results of the study show that for each of the energy components and growth variables, own shocks were more profound and there were evidences of substitutability of shocks implying that as own shocks reduce, the shocks from other variables increase in magnitude while in other cases, shocks were sinusoidal in nature. The study recommends that comprehensive energy consumption, labour and capital accumulation, and growth-enhancing policies should be designed for the Nigerian economy and in the context of such policies all the variables adopted in the VAR models are to be treated as target and instruments of energy consumption, capital accumulation, labour participation and economic growth.